The Impact of Service Quality on Hemodialysis Patient Satisfaction: A Literature Review - Sunarti Sunarti; Karmila Br Kaban; Elis Anggeria (Universitas Prima Indonesia, 2026)
Hemodialysis Unit is performed on patients with End-Stage Renal Failure (ESRD) and a background of various pre-existing health problems. Hemodialysis management requires the skills of competent nurses and is supported by hospital management, particularly good service management, to improve patient satisfaction. The study utilizes secondary data by analyzing journals obtained from 2020 to 2025. This study uses the Preferred Reporting Items for literature review and Meta-Analyzes (PRISMA) approach. The article search process was conducted electronically. Data were obtained from the Scopus database and Google Scholar, Pubmed, DOAJ and GARUDA, the literature review used the keywords service quality, patient satisfaction, and hemodialysis. The results obtained in this study obtained 21 articles, 6 articles were not selected because they were not full-text reviews (3 from Scopus, and 3 from Google Scholar). There were 8 articles that were not analyzed because of qualitative research, and a total of 33 duplicate articles were excluded. Finally, 7 articles were selected for review. From the results of the literature review, it was found that good service quality in the hemodialysis room will increase high satisfaction for patients undergoing hemodialysis. From the results of the study, there are several factors that support improved health services such as service, facilities, atmosphere, and short waiting times have a positive effect on patient satisfaction. Good quality healthcare services in the hemodialysis room increase patient satisfaction. Many factors contribute to service quality, including cleanliness, waiting times, facilities, and the hemodialysis treatment environment.